2017
DOI: 10.1093/eurheartj/ehx527
|View full text |Cite
|
Sign up to set email alerts
|

Women with hypertrophic cardiomyopathy have worse survival

Abstract: Women with HCM present at more advanced age, with more symptoms, worse cardiopulmonary exercise tolerance, and different haemodynamics than men. Sex is an important determinant in HCM management as women with HCM have worse survival. Women may require more aggressive diagnostic and therapeutic approaches.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

17
174
4
8

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 180 publications
(203 citation statements)
references
References 65 publications
17
174
4
8
Order By: Relevance
“…A study from the Mayo Clinic enrolled 3673 HCM patients (1661 women and 2012 men) during 1975–2012, with a median follow‐up period of 10.9 years, and demonstrated that that women had more symptoms, worse cardiopulmonary exercise tolerance, different changes in haemodynamics and lower survival rates than men. In multivariable modelling, female sex remained independently associated with mortality, suggesting that women might require more aggressive diagnostic and therapeutic approaches (Geske et al., ). Similar results were demonstrated in another study from China, with 621 HCM patients (161 women and 460 men) from 1999 to 2011, with a median follow‐up period of 4 years.…”
Section: Discussionmentioning
confidence: 99%
“…A study from the Mayo Clinic enrolled 3673 HCM patients (1661 women and 2012 men) during 1975–2012, with a median follow‐up period of 10.9 years, and demonstrated that that women had more symptoms, worse cardiopulmonary exercise tolerance, different changes in haemodynamics and lower survival rates than men. In multivariable modelling, female sex remained independently associated with mortality, suggesting that women might require more aggressive diagnostic and therapeutic approaches (Geske et al., ). Similar results were demonstrated in another study from China, with 621 HCM patients (161 women and 460 men) from 1999 to 2011, with a median follow‐up period of 4 years.…”
Section: Discussionmentioning
confidence: 99%
“…Так, в работе Olivotto I, et al и 47±23 года, соответственно). Аналогичные резуль-таты получены в ряде других работ [3][4][5]11]. При изучении гендерных особенностей в группе пациентов пожилого возраста с идиопатической ГКМП Северо-Западного региона России выявлено преобладание женщин (1:1,7), что вероятно, связано с меньшей продолжительностью жизни мужчин.…”
Section: Discussionunclassified
“…В работе Olivotto I, et al (2005) показано, что жен-щины на момент верификации ГКМП также характе-ризовались наличием более выраженных симптомов, чем мужчины (класс NYHA 1,8±0,8 против 1,4±0,6), что согласуется с другими литературными данными [3][4][5]11]. Однако, следует отметить, что авторы ана-лизировали тяжесть ХСН в пределах одного функцио-нального класса, соответствующего легкой и умерен-ной ХСН.…”
Section: Discussionunclassified
See 2 more Smart Citations